Optimization of thermal oxidation of electrodes for the performance enhancement in all-vanadium redox flow betteries - Ghimire, Purna Chandra (2020)
Thermal oxidation of a graphite felt in air is the most widely used electrode activation method to enhance the performance of a vanadium redox flow battery. It has been reported extensively, but almost all previous studies used individual treatment protocols with only few parameter variations. In this paper, treatment time and temperature were varied systematically along with in-depth physicochemical and electrochemical analysis. Prolonged treatment time is chosen for oxidation at lower temperatures aiming at low material loss rates, whereas shorter periods are applied at higher treatment temperatures, which are associated with elevated material loss. Among the electrodes treated with various protocols, the best performance is observed with electrodes oxidized at 750 C for 5 min. This study is important for both, reproducibly preparing samples at lab scale as well as commercial developers, where optimized and cost-effective pretreatment plays a significant role.